Independent Suture Tape Internal Brace Reinforcement of Bone–Patellar Tendon–Bone Allografts: Biomechanical Assessment in a Full-ACL Reconstruction Laboratory Model - Smith, Patrick A.; Bradley, James P.; Konicek, John; Bley, Jordan A.; Wijdicks, Coen A. (The Journal of Knee Surgery, 2019)
Internal bracing for anterior cruciate ligament (ACL) surgery is a relatively new concept. The purpose of this study was to evaluate the effects of an “independent” button-fixed internal brace on the biomechanical properties of ACL reconstruction in a full-construct experimental model. Three groups (n = 10 each) were tested in a full-construct porcine-bone model with human bone–patellar tendon–bone allografts using different reconstruction techniques: interference screw fixation on femur and tibia (S-S group), adjustable-loop device (ALD) fixation on the femur with tibial interference screw without suture tape (ALD-S group), and with internal brace (ALD-S-IB group). Measured outcomes included cyclic displacement, stiffness, and ultimate load to failure. The ALD-S-IB group (2.9 ± 0.8 mm) displaced significantly less than the ALD-S (4.2 ± 0.9 mm; p = 0.015) and S-S group (4.3 ± 1.1 mm; p = 0.017). No significant difference was found between the ALD-S and the S-S group. Construct stiffness was significantly higher for the ALD-S-IB group (156 ± 23 N/mm) and the ALD-S group (122 ± 28 N/mm) than for the S-S group (104 ± 40 N/mm; p = 0.003 and p = 0.0042), but there was no significant difference between both ALD groups. Similarly, ultimate loads in the ALD-S-IB (758 ± 128 N) and the ALD-S groups (628 ± 223 N) were significantly greater than in the S-S group (416 ± 167 N; p < 0.001 and p = 0.025), but there was no significant difference between ALD groups. Adding an internal brace reinforcement to an ALD in a full-construct experimental model significantly decreased cyclic displacement by 31% without increasing construct stiffness or ultimate load significantly. These results indicate that suture tape internal bracing of bone–patellar tendon–bone allograft ACL reconstruction decreases cyclic displacement during experimental testing, which has clinical implications regarding initial construct stability.
Keywords: anterior cruciate ligament; bone–tendon–bone; internal brace; biomechanics